Choice of stent and outcomes after treatment of drug‐eluting stent restenosis in highly complex lesions1. Issue 1 (17th April 2012) - Freixa, Xavier; Almasood, Ali S.; Khan, Sohail Q.; Mackie, Karen; Osten, Mark; Ing, Douglas; Overgaard, Christopher B.; Horlick, Eric M.; Seidelin, Peter H.; Džavík, Vladimír
Abstract Objectives Our aim was to compare the outcomes of a same versus different drug‐eluting stent (DES) implantation strategy for the treatment of DES instent restenosis (ISR). Background The absence of clear data renders the treatment of DES ISR one of the most challenging situations in interventional cardiology. Methods We identified all cases of DES ISR treated with a second DES between January 2004 and January 2009. The lesions were divided into those treated with the same DES as the initial one that restenosed and those treated with a different DES. The main end‐point was repeat target lesion revascularization (TLR). Results We included 116 patients with a total of 132 lesions. The patient population was highly complex: 55.5% with diabetes, 56% with type‐C lesions, 15.9% with lesions previously stented with BMS and 18.2% with fluoroscopic evidence of stent fracture. A same and different stent strategy was conducted in 41 lesions (31%) and 91 lesions (69%), respectively. Overall TLR was 31.1% and occurred in 46.3% of patients treated with the same stent and 24.4% of those with a different stent (P = 0.012). Multivariable analysis found same stent strategy (OR 2.84, 95%CI 1.23–6.57;P = 0.014) and occurrence of stent fracture (OR 4.03, 95%CI 1.33–12.01;P = 0.012) to be the only independent predictors of TLR after a median follow‐up of 20.4 [12.1–30.2] months. Conclusions In highly complex lesions, DES implantation for DES ISR is linked to a high need of future revascularization. An association between implanting a DES type other than the original and lower rate of TLR is suggested. © 2012 Wiley Periodicals, Inc.